Revision of the elusive ant genus Rhopalomastix (Hymenoptera, Formicidae, Myrmicinae) in Thailand based on morphology and DNA barcodes, with descriptions of three new species – Corrigendum - Wang, Wendy Y.; Yong, Gordon W.J.; Jaitrong, Weeyawat (European Journal of Taxonomy, 2021)
The present corrigendum corrects errors that occurred in: Wang W.Y., Yong G.W.J. & Jaitrong W. 2021. Revision of the elusive ant genus Rhopalomastix (Hymenoptera, Formicidae, Myrmicinae) in Thailand based on morphology and DNA barcodes, with descriptions of three new species. European Journal of Taxonomy 739: 117–157. https://doi.org/10.5852/ejt.2021.739.1271